Mutu Fisik Dan Teknik Pematahan Dormansi Benih Kayu Kuku (Pericopsis mooniana (Thw.) Thw.) - Arum Sekar Wulandari; Afrida Rizka Farzana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The presence of Pericopsis mooniana (Thw.) Thw. in nature is endangered. Meanwhile, Pericopsis mooniana plants have its obstacles in generative propagation because the seeds have mechanical dormancy. Studies carried out to: (1) observe the morphology of pods, seeds and sprouts of Pericopsis mooniana; (2) determine the physical quality of Pericopsis mooniana seeds, and (3) analyze the proper dormancy breaking treatment for Pericopsis mooniana seeds. Research is conducted in laboratories and in greenhouses. The physical quality of the seeds measured was the weight of 1,000 seeds and the moisture content. The treatment for breaking the dormancy of the Pericopsis mooniana seeds were control, scarification of the seeds using nail clippers and soaking in hot to cold water for 48 hours. Morphologically, the fruit of Pericopsis mooniana is pod-shaped, with orange seeds, oval-shaped and curved edges. Pericopsis mooniana sprouts include in the epigeal type. In 1 kg of weight there are ± 4,000 Pericopsis mooniana seeds, with the post harvest seed moisture content amounting to 7.62%. The dormancy breaking treatment of Pericopsis mooniana seeds increased seeds germination by 60% compared to controls. The scarification of Pericopsis mooniana seeds using nail clippers for breaking mechanical dormancy is the best treatment because it can increase the number of seeds germinating in a short time and simultaneously. Key words: breaking seed dormancy, morphology, Pericopsis mooniana, physical quality, seed scarificatio